CD7‐targeting pro‐apoptotic extracellular vesicles: A novel approach for T‐cell haematological malignancy therapy - Bei Zhang; Jianqiang Chen; Jiming Chen; Yingying Shen; Yinghu Chen; Shibo Wang; Chengyan Zhang; Yuzhou He; Huajun Feng; Jiaoli Wang; Zhijian Cai (Journal of Extracellular Vesicles)
Abstract T‐cell haematological malignancies progress rapidly and have a high mortality rate and effective treatments are still lacking. Here, we developed a drug delivery system utilizing 293T cell‐derived extracellular vesicles (EVs) modified with an anti‐CD7 single‐chain variable fragment (αCD7/EVs). Given the challenges of chemotherapy resistance in patients with T‐cell malignancy, we selected cytochrome C (CytC) and Bcl2 siRNA (siBcl2) as therapeutic agents and loaded them into αCD7/EVs (αCD7/EVs/CytC/siBcl2). We found that αCD7/EVs efficiently targeted and were internalized by human T‐ALL Molt‐4 cells. In addition, the interaction between αCD7 and CD7 switched the EV entry pathway in Molt‐4 cells from macropinocytosis‐dependent endocytosis to clathrin‐mediated endocytosis, thereby reducing EV‐lysosome colocalization, ultimately improving CytC delivery efficiency and increasing the cytotoxicity of nascent EVs from EV‐treated Molt‐4 cells. Notably, αCD7/EVs/CytC/siBcl2 demonstrated similar efficacy against both Molt‐4 and chemotherapy‐resistant Molt‐4 cells (CR‐Molt‐4). Furthermore, αCD7/EVs/CytC/siBcl2 exhibited high safety, low immunogenicity and minimal impact on human T cells. Therefore, αCD7/EVs/CytC/siBcl2 are promising therapeutic approaches for treating CD7+ T‐cell malignancies.